Phylogenetics and Mobilization of Genomic Traits of Cephalosporin-Resistant Escherichia coli Originated from Retail Meat - Ewelina Iwan; Magdalena Zając; Arkadiusz Bomba; Małgorzata Olejnik; Magdalena Skarżyńska; Bernard Wasiński; Kinga Wieczorek; Katarzyna Tłuścik; Dariusz Wasyl (Pathogens, 2024)
Contaminations with cephalosporin-resistant Escherichia coli across the food chain may pose a significant threat to public health because those antimicrobials are critically important in human medicine. The impact of the presented data is especially significant concerning Poland’s role as one of the leading food producers in the EU. This work aimed to characterize the genomic contents of cephalosporin-resistant Escherichia coli (n = 36) isolated from retail meat to expand the official AMR monitoring reported by EFSA. The ESBL mechanism was predominant (via blaCTX-M-1 and blaSHV-12), with the AmpC-type represented by the blaCMY-2 variant. The strains harbored multiple resistance genes, mainly conferring resistance to aminoglycosides, sulfonamides, trimethoprim, tetracyclines. In some isolates, virulence factors—including intimin (eae) and its receptor (tir) were detected, indicating significant pathogenic potential. Resistance genes showed a link with IncI1 and IncB/O/K/Z plasmids. Cephalosporinases were particularly linked to ISEc9/ISEc1 (blaCTX-M-1 and blaCMY-2). The association of virulence with mobile elements was less common—mostly with IncF plasmids. The analysis of E. coli isolated from retail meat indicates accumulation of ARGs and their association with various mobile genetic elements, thus increasing the potential for the transmission of resistance across the food chain.